DEPICTING URGENCIES OF THE INTEGRATION OF CYBERTEXT CONTEXT IN EDUCATIONAL PRAGMATICS WITH A SOCIOSEMIOTIC MULTIMODAL PERSPECTIVE (MEMERIKAN URGENSI INTEGRASI KONTEKS SIBERTEKS DALAM PRAGMATIK EDUKASIONAL BERPERSPEKTIF MULTIMODAL SOSIOSEMIOTIK) - R. Kunjana Rahardi (Jurnal Gramatika, 2022)
This study aims to describe the urgency of integrating cybertext context aspects in pragmatic educational learning with a social semiotic multimodality perspective. The data for this research are the numbers obtained from respondents' responses to the Likert scale research instrument submitted via the google form. The population of this study was students of the Indonesian language education master's program. At the same time, the research sample was students of the Indonesian language education master's program, FKIP, the University of Sanata Dharma, who had received pragmatic educational lectures. The responses to the instruments presented to them were then analyzed with simple descriptive statistics to obtain figures that describe the depth of understanding and perception of the urgency of integrating cybertext contexts into educational pragmatics learning. This research has produced two findings in response to the formulation of the research questions. First, students' understanding of aspects of the cybertext context in a semiotic social multimodality perspective is still low. Second, the urgency to integrate aspects of the context and function of the cybertext context into pragmatic educational learning based on semiotic social multimodality is very high.